TRADE DURING PRE-SRIWIJAYA (4th–5th Centuries AD) - Triwurjani Triwurjani (Berkala Arkeologi, 2011)
Since early century AD until 5th century AD South Sumatra had been inhabited by communities that were composed in solid social integrations in form of local chiefdoms. Researches concluded that in 4th century AD there were settlements of communities in the East coast of Sumatera. It was believed that these communities had made cantacts with India and Chinese traders, as well as with traders from other countries, Karang Agung Site is one of the sites that had been inhabited by humans during the above period. It is located in South Sumatra in the east coast of Sumatra. There are a number of variables that show the importance of this site, they are: its location which was near water (Musi tributary, moats); the existence of boat stake and various artifacts that were assumed to be trade commodities (stone and glass beads, fine-paste pottery, gold jewelry in forms of earrings and rings) and remains of a boat; its location in international trade route. According to Van Leur, one of the two main trade routes in Asia is the “silk road” that covers China, India and up to Europe. It passed through Central Asia, Turkistan, and the Mediterranean Sea, which had contacts with Indian travelers/traders. This paper is made in an attempt to re-emphasize the existence of the site of Karang Agung, which is based on its natural landscape that was a tidal swamp with very limited sources of fresh water. Despite all that, its inhabitants were very advanced in the field of trade. There must have been some factors that forced this area to become the buffer zone in an international trade route between the open seas and the interior areas.